Temporal arteritis presenting with tongue necrosis - Kumarasinghe, Anuttara Panchali (BMJ Case Rep, 2012)
Spontaneous glossodynia is uncommon and glossodynia progressing to necrosis is especially rare. Although the commonest cause of lingual necrosis is giant cell arteritis, only a few cases of a new diagnosis of giant cell arteritis, clinically presenting with isolated lingual necrosis, have been reported.